Reconstruction of the Ancestral Sajen Tradition by Buddhists - Sukarti, Sukarti (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to describe the implementation of the ancestral offering tradition and analyze the reconstruction of the ancestral offering tradition by the Buddhists. The type of qualitative research with a case study approach. Research at Dharma Dwipa Temple, Sodong, Ponorogo. Data collection techniques used observation, interviews, and documentation. Data analysis used the Milles and Huberman model. Test the validity of the data with triangulation of techniques and sources. The results of the study found that the offering tradition was carried out in various celebration events. Behavior towards the offering tradition describes the cultural life of the Javanese people, which is inseparable from ritual symbols. The reconstruction that occurs in the offering tradition refers to the concept of incorporating several innovations without changing their original nature and characteristics. Changes that occur in the offering tradition lead to three principles, namely: 1) understanding the values ​​of the offering tradition, 2) adjusting the elements (means) of offerings, and 3) integrating into Buddhist rituals. The Buddhist offering tradition refers to the practice of Buddhist teachings, namely the Pattidāna tradition. The Tirokudda